2016
DOI: 10.1038/srep32611
|View full text |Cite
|
Sign up to set email alerts
|

Refinement of the androgen response element based on ChIP-Seq in androgen-insensitive and androgen-responsive prostate cancer cell lines

Abstract: Sequence motifs are short, recurring patterns in DNA that can mediate sequence-specific binding for proteins such as transcription factors or DNA modifying enzymes. The androgen response element (ARE) is a palindromic, dihexameric motif present in promoters or enhancers of genes targeted by the androgen receptor (AR). Using chromatin immunoprecipitation sequencing (ChIP-Seq) we refined AR-binding and AREs at a genome-scale in androgen-insensitive and androgen-responsive prostate cancer cell lines. Model-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
112
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(126 citation statements)
references
References 88 publications
9
112
1
Order By: Relevance
“…Analysis of the binding sequences present in the AR-derived peaks showed that classical palindromic ARE sequences were very poorly represented in fibroblasts, which suggests that the AR is likely to bind to chromatin via cofactors or other transcription factors [20]. AP1 was identified as a co-factor for AR in the PShTERT-AR cell line [34], however we did not observe many AP1 sites in our data.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Analysis of the binding sequences present in the AR-derived peaks showed that classical palindromic ARE sequences were very poorly represented in fibroblasts, which suggests that the AR is likely to bind to chromatin via cofactors or other transcription factors [20]. AP1 was identified as a co-factor for AR in the PShTERT-AR cell line [34], however we did not observe many AP1 sites in our data.…”
Section: Discussioncontrasting
confidence: 53%
“…This has revealed a transcriptional role for AR in tumour cells regulating cell proliferation, metabolism, survival and DNA repair [18,19]. Prostate cancer cell lines have also been used to determine the changes in AR transcriptional networks in both a hormonenaïve-and castrate-resistant setting and numerous studies have revealed distinct binding profiles in the androgen-independent setting [13,17,18,20,21]. More recently, the genomic binding profile of AR variants have also been explored and have been shown to compensate for full length AR in an endocrine therapy-like setting [22].…”
Section: Introductionmentioning
confidence: 99%
“…In doing so, these consortia have also generated remarkable volumes of publically available data with which to interrogate DNA methylation patterns and relationships to gene expression and cell phenotypes. In cancer it is clear that the TF-genome interactions are corrupted [82,83,84,85] and “re-wired” [86,87,88], for example, by somatic mutations and endogenous structural variants that disrupt TF binding. A major driver of addressing global DNA methylation in cancer has been the development of large cancer genome studies, for example the Cancer Genome Atlas (TCGA) in which virtually all 30,000 tumors in the archive have been screened with Illumina microarray approaches.…”
Section: The Transition From Epigenetic To Epigenomic Analyses Of mentioning
confidence: 99%
“…Rather, recent ChIP-Seq data have clarified that AR binds to selective AREs because of less stringent sequence requirements for the 3′ hexamer (Sahu, et al 2014). Recent bioinformatics-guided modeling of the ARE motifs derived from similar high-throughput studies indicated that only a minority of the AREs fit perfectly the consensus AGAACAnnnTGTTCT 15-mer motif (Wilson, et al 2016). The majority of AREs corresponded to “imperfect” AREs in which mismatches of 1 or more basepairs from the consensus motif occur.…”
Section: Diversity In Ar-dna Interactionsmentioning
confidence: 99%
“…Consistent with other reports (see for instance (Massie, et al 2007; Wang, et al 2007)), for a significant number of AR binding sites only one ARE half site that corresponds to a perfect hexamer was present. Increased levels of degeneracy of the ARE have been linked with decreased level of transcriptional output of those sites (Wilson et al 2016). As technology became more sensitive and allowed for higher resolution scanning of the ARE motif and its surrounding sequence, more details could be derived on the genomic regions occupied by AR.…”
Section: Diversity In Ar-dna Interactionsmentioning
confidence: 99%